A pictorial essay on fetal rabbit anatomy using micro‐ultrasound and magnetic resonance imaging. (22nd November 2013) - DeKoninck, Philip; Endo, Masayuki; Sandaite, Inga; Richter, Jute; De Catte, Luc; Van Calster, Ben; Toelen, Jaan; Himmelreich, Uwe; Claus, Filip; Deprest, Jan
ABSTRACT Introduction With this pictorial essay, we aimed to provide gestational age specific reference ranges of relevant fetal structures using micro‐ultrasound, as well as its correlation with postmortem MRI and whole body sections. Material and Methods Time‐mated pregnant rabbits (n = 24) were assessed once at various gestational ages in the second half of pregnancy (15, 17, 21 to 23, 25 to 28, and 30 to 31 days; term = 31 days). We obtained biometric data, together with Doppler flow patterns in the ductus venosus, umbilical artery and umbilical vein. After euthanasia, micro‐ultrasound images were compared with images obtained by 9.4 Tesla MRI and whole body paraffin sections at 15, 23, 26, and 28 days. Results We constructed biometric normative curves, which showed a significant correlation with gestational age. The pulsatility index (PI) in the umbilical artery decreased with gestation (PI = 5.746–0.2969(GA) + 0.004931(GA)2; R2 = 0.30), whereas pulsatility index for veins (PIV) in the ductus venosus remained constant (median PIV = 0.82 (0.60–1.12)). In this report, we provide an anatomical atlas of fetal thoracic development using both micro‐ultrasound and MRI. Conclusion We describe anatomical fetal leporine development as can be visualized by micro‐ultrasound and MR imaging. The reported reference ranges may be useful for researchers using the fetal rabbit model. © 2013 John Wiley & Sons, Ltd.